Development of a Biology Module Based on Science Process Skills for Class XI Madrasah Aliyah Students - Masrina Sitanggang; Rohani; Husnarika Febriani (Marga: Journal Of Innovation and Creatifity, 2024)
The development of a Science Process Skills Based Module for class XI Madrasah Aliyah students has been carried out and implemented in class XI of Masrasah Aliyah Nurul Hakim Tembung. This research development aims to produce capital based on science process skills that meets the criteria of being valid, practical and effective. This type of research is Research & Development (R&D) using the Borg & Gall procedure modified by Sugiyono. The test subjects in this research were class XI students, small-scale trials were carried out with 10 students and usage trials were carried out with 27 students. The research has reached the final stage, namely ten stages in R & D research, namely (1) Potential and Problems (2) Data Collection (3) Product Design (4) Design Validation (5) Design Revision (6) Product Trial (7) Revision Product (8) Use Trial (9) Product Revision (10) Mass Production. Based on the results of product validation from several experts, the assessment from media experts was 77% with very feasible criteria, and the material expert assessment was 79% with the category very suitable for use. The assessment results from educators were 94.31% with very suitable criteria and student respondents got a percentage of 87% with very suitable criteria for use. This learning module has met the effective criteria based on the N-Gain test results, a score of 75.81%.